HAZARDOUS WASTE SHOULD BE MANAGED PROPERLY FOR DEVELOPMENT OF BETTER WASTE MANAGEMENT STRATEGIES - Maulida, Afina; Oktaviani, Aliyah; Pakpahan, Helen Steavy; Wikaningrum, Temmy (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2022)
Hazardous waste products and trash disposal methods are vital to society. Over the last few decades, the production of hazardous waste has increased in tandem with population growth, industrialization, increasing urbanization. The constantly increasing industry sector has resulted in the creation of a massive volume of hazardous waste. As a result, enough care must be taken throughout the collection, processing, transporting, and disposal of hazardous materials in order to reduce environmental dangers, as it cannot be disposed of in the environment since it is. That study looks at hazardous wastes, their many types, and how they are managed. Improved strategies for identifying the most convenient and ecologically friendly hazardous waste medication and disposal techniques are required. This document discusses the numerous hazardous wastes created by industry, as well as the nature of those wastes and several methods that can be used for managing the hazardous waste.